Low-frequency processes at interaction of ion flows with relativistic electron beams - Balakirev, V.A.; Onishchenko, N.I.; Onishchenko, I.N. (Вопросы атомной науки и техники, 2005)
Nonlinear process of excitation of LF oscillations is investigated at radial injection of ion stream into the drift chamber in which tubular REB is propagated. The mechanism of LF ion oscillation excitation is investigated.